Beethoven: 2 Symphonie - Kolb, Alois, 1875-1942 (artist):::Creator:::::::::::: (Vienna; Karl König, printed by M. Jaffó; Austria)
Allegorical image inspired by Beethoven's Second Symphony; no. IV of Kolb's Beethoven cycle.